Intention to receive Latent Tuberculosis Infection (LTBI) treatment and its associated factors among healthcare workers in a Malaysian teaching university hospital - El Seifi, Omnia Samir; Zakaria, Wan Muhammad Zainol; Mansor, Zawiah (Public Library of Science, 2024)
The acceptability of latent tuberculosis infection (LTBI) therapy remains low among healthcare workers (HCWs). Up to 10% of LTBI cases can reactivate into active tuberculosis, posing risks to HCWs and patients. Understanding HCWs’ intention to undergo LTBI treatment is crucial for designing effective management policies, especially where no LTBI policy exists. This cross-sectional study investigated the intention to receive LTBI therapy and its associated factors among HCWs in a Malaysian teaching hospital. The study was conducted from 5th to 30th May 2023, in a hospital without an LTBI screening program. Stratified random sampling was used to select HCWs, excluding those undergoing TB or LTBI therapy. Respondents completed a questionnaire measuring intention to receive LTBI treatment, LTBI knowledge, attitude, perceived norm, and perceived behavioral control. Of the 256 respondents, the majority were female (63.7%), under 35 years old (64.45%), had no comorbidities (82.0%), and worked in clinical settings (70.3%). However, 60.5% of respondents had low LTBI knowledge and 60.5% held unfavorable attitudes toward LTBI treatment. Despite this, 53.5% of respondents intended to undergo LTBI therapy if diagnosed. Factors positively associated with this intention included being female [aOR: 2.033, 95% CI: 1.080–3.823], having high LTBI knowledge [aOR 1.926, 95% CI: 1.093–3.397], had favorable attitude [aOR 3.771, 95% CI: 1.759–8.084], and strongly perceiving social norms supportive of LTBI treatment [aOR 4.593, 95% CI: 2.104–10.023]. These findings emphasize the need for an LTBI management policy in the teaching hospital. To boost HCWs’ intention and acceptance of LTBI treatment, a focused program improving knowledge, attitude, and perception of social norms could be introduced.